2017
DOI: 10.5539/jmbr.v7n1p106
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Food Consumption Patterns in Patients with Gastric Cancer in Mazandaran

Abstract: Gastric cancer is one of the most common types of cancer. There are geographical and racial differences in the prevalence of gastric cancer in different societies. The present study aims to investigate the food consumption patterns in patients with gastric cancer in Mazandaran.This case-control study was conducted among 100 patients with gastric cancer and 200 healthy controls. Two questionnaires including demographic information, and food frequency were completed by all participants.The mean frequency of cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Many studies have found that the risk of GC is associated with many dietary factors; 8 in particular, the high intake of vegetables and fruits can be protective factors. 50 In recent years, soy-based food has received considerable attention because of its numerous beneficial phytochemicals such as isoflavones, which have some anticancer properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have found that the risk of GC is associated with many dietary factors; 8 in particular, the high intake of vegetables and fruits can be protective factors. 50 In recent years, soy-based food has received considerable attention because of its numerous beneficial phytochemicals such as isoflavones, which have some anticancer properties.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 For example, a recent cohort study in Japan suggested that moderate intake of soy could reduce the mortality of cancer in the Japanese male population. 7 Based on this, much research have been carried out to explore the relationship between soy-based food and the risk of GC 8 and also to ascertain which substances in soybean affect GC. 5 However, results from these studies were inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…11 Therefore, because of the wide use of cooling and refrigerating devices, there has been an increase in people's access to fruits throughout the year, which has had a significant role in reducing the incidence of GC. 17,18 The results of GBD 2017 showed that the age-standardized summary exposure value of diet low in fruits in Iran has decreased from 23.6 (17.8-28. All these show that the use of fresh fruits and vegetables in Iran has increased during 1990 to 2017 (1).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that regular and daily use of fresh fruits and vegetables, especially citrus fruits, onions, and garlic plays an important role in the prevention of GC 11 . Therefore, because of the wide use of cooling and refrigerating devices, there has been an increase in people's access to fruits throughout the year, which has had a significant role in reducing the incidence of GC 17,18 . The results of GBD 2017 showed that the age‐standardized summary exposure value of diet low in fruits in Iran has decreased from 23.6 (17.8‐28.6) in 1990 to 15.4 (9.7‐21.0) per 100 in 2017.…”
Section: Discussionmentioning
confidence: 99%